(untitled) (Journal of human and social sciences, 2022)
This study aims to evaluate the quality of undergraduate accounting education in Libyan universities from the perspective of accounting graduates. The rapid growth of higher education in Libya, including an increase in student numbers, graduates, academic programs, and attention to accreditation and quality assurance, makes assessing educational quality essential. The study focuses on identifying the factors that influence accounting education quality, highlighting both strengths and weaknesses in the current system, and examining how these factors affect graduates’ preparedness for the labor market. The research problem stems from concerns that accounting education may not fully meet the standards required for producing competent graduates who can contribute effectively to economic development. To address this, the study applied a descriptive-analytical approach, combining a review of relevant literature with empirical data collected via a structured survey of accounting graduates. Statistical analyses, including measures of central tendency, standard deviation, one-way ANOVA, and multiple regression, were conducted using SPSS to test the study hypotheses and assess the perceived quality of accounting education. The findings are intended to provide insights into areas that require improvement, inform policy decisions, and propose recommendations for enhancing the quality of accounting education in Libya. Ultimately, the study seeks to contribute to the development of a higher education system capable of producing highly qualified accounting professionals who meet national and international standards.